(untitled) (GEOmedia, 2009)
Hinarche 2008: a scientific expedition on a far glacier In summer 2008 an Italian Scientific expedition performed a detailed glaciological survey of the Hinarche Glacier, Karakoram, Pakistan. The goal of the expedition was the characterization of the features of one of the main glacier of the Bagrot Valley. Glacier melting water represents one of the main resources of Pakistan Northern Area communities. The melting water flowing in the steep irrigation channels is the driving element supporting local economies, mainly based on agriculture and farming. Evaluating the availability of water resource is one of the difficult tasks covered by glaciology. In the Bagrot valley a team of researchers performed a dense campaign of glaciological measurements to identify the main morphological aspects of the Hinarche Glacier. The study requested the use in field of geodetic GPS receivers. Furthermore, the field activity trained local researchers which will give continuity to these monitorino campaigns, who in turn will update data sets from these areas which form part of the WGMS (World Glacier Monitoring Service) database.